General mental ability moderates the link between confidence and integrity test scores. (1st March 2018) - Cunningham, Mitchell L.; Douglas, Heather; Boag, Simon
Abstract: The present study examined whether general mental ability (GMA) moderated the link between confidence and integrity test scores. Participants were 477 Australian adults who completed an online survey that gauged GMA, confidence in the accuracy of responses to GMA items, and the Hilson Safety/Security Risk Inventory as a measure of integrity. Results indicated that confidence was a negative predictor of both Safety Risk and Lack of Hostility/Anger Control. An interaction effect was also found in that overconfident individuals (i.e., low GMA and high confidence) were less likely to report more aggression and hostility on the job. The implications of the findings are discussed. Highlights: One's level of confidence in own cognitive ability was found to predict integrity. Overconfident individuals were less likely to display safety risk behaviours. Overconfident individuals reported better hostility/anger control in the workplace.